CO2 Permeability Analysis of Caprock Containing a Single Fracture Subject to Coupled Thermal-Hydromechanical Effects - Wang, Huidong; Su, Haijian; Jing, Hong-wen; Yin, Qian (Mathematical problems in engineering, 2017)
Coupled THM (thermal-hydromechanical) processes have become increasingly important in studying the issues affecting subsurface flow systems. CO2 permeability of the fracture in caprock is a key factor that affects sealing efficiency of caprock. A new model associated with coupled THM processes that shows a good reliability was derived. Then, based on the COMSOL multiphysics software, a series of numerical calculations were performed on caprock models with a single fracture subject to coupled THM effects. Transmissivity of the fracture as a function of fracture angle, overburden pressure, fluid pressure difference, injected CO2 temperature, and the initial fracture aperture was elucidated, respectively. Average transmissivity of the fracture undergoes an increase by 1.74 times with the fracture angle (45°–90°), 2-3 orders of magnitude with the fluid pressure difference (5–30 MPa), and 4-5 orders of magnitude with the initial fracture aperture (0.05–0.5 mm), while it decreases by 3-4 orders of magnitude as overburden pressure increases from 30 to 80 MPa. Injected CO2 temperature has a small impact on the fracture permeability. This work provides an alternative tool to enrich the numerical modeling for the assessment of CO2 caprock sealing efficiency.